THE IMPACT OF BILINGUAL LEARNING ON STUDENTS SELF-CONFIDENCE IN ACADEMIC AND SOCIAL DOMAINS - Nuranisa; Syamsiarna Nappu; Achmad Basir (English Language Teaching Methodology, 2025)
This research aims to find out whether there is an influence of bilingual learning on students’ self-confidence in their academic achievement and social communication, for students in grades V and VI of IOP Primary School. The population of this research was classes V and VI and the sample consisted of 8 students. Data collection used a quantitative descriptive method with a questionnaire to find out how students responded to bilingual learning regarding their self-confidence and used observation as a support for the questionnaire. The results show that the influence of bilingualism on students’ self-confidence in academic achievement is in the very high category (76.5%). While the influence on social communication is in the high category (75℅) all students on average agree that bilingual learning has a great influence on their self-confidence, bilingual learning makes students enthusiastic about learning and motivates them to be active in learning, self-confidence is influenced by Bilingualism is also beneficial for their academic achievement and communication.